Low-cost seepage meters for flow measurement and water sampling in stream bed/sediments interface of mountain rivers - Carias, Victor Alves [UNESP]; Vilanova, Mateus Ricardo Nogueira [UNESP] (Lepidus Tecnologia, 2020)
The study of hyporheic flow has gained attention in recent decades, due to the recognition of the various physical, geochemical and biological processes that occur at its interface. These processes directly and indirectly influence ecosystems and the water resources availability. The importance and complexity of the hyporheic zone is increased in mountain rivers, located in regions of high conservation relevance and great hydrometeorological variability. Nevertheless, the use of traditional seepage meters may be unfeasible in this type of river, due to their physical characteristics (bed sediments size and bed geometry) and the difficulty of access to certain mountainous areas. Given the above, this paper reports the development and evaluation (in laboratory and in loco) of two types of low*cost seepage meters, built with PVC pipes and industrial buckets. An experimental bench with discharge control/measurement, simulating a river bed, was developed for the tests, whose results were evaluated based on the calculation of the Type “A” standard uncertainty. The tests showed that the meter built with industrial bucket (M2) can be used in real measurements, while the meter made with PVC pipe (M1) did not perform well. During the tests, the M2 presented a deviation of approximately 12% in relation to the bench reference discharge, with a standard uncertainty of 0.40 L.m*2.
Medidores de baixo custo para a quantificação de fluxo e coleta de amostras de água na interface leito/sedimentos em rios de montanha
Keywords: Baseflow; Mountain hydrology; River*aquifer interaction